Religion and Well-Being: The Mediating Role of Positive Virtues - Sharma, Swati (Journal of religion and health, 2019)
Researchers have consistently advocated positive associations between religion and well-being. The present research takes a step forward and explores potential mechanisms behind the same. The mediating role of a surprisingly neglected mechanism, positive virtues, specifically gratitude, forgiveness and altruism, is studied through a quantitative study on a sample of 220 adult respondents residing in Delhi NCR. The participants adhered to one of the six major religions present in India. Mediational analysis revealed that gratitude mediated the relationship between religiosity, spirituality and well-being via two pathways of forgiveness and altruism. The implications for researchers and practitioners working in the field of mental health are discussed.